Pemanfaatan Teknologi Firebase Pada Perancangan Aplikasi Reservasi Salon Berbasis Android - Sari, Agnesta Linda; Sutarman, Sutarman (Jurnal Informatika, 2024)
This study developed a salon reservation application based on Android, utilizing Firebase technology as its backend. The application aims to simplify the online reservation process and enhance the efficiency of salon operational management. The methods applied include observation, system design, implementation, and testing. Data was collected through interviews with salon owners, employees, and customers to determine system requirements. The application was built using the Kotlin programming language on the Android Studio platform. Firebase was utilized to provide user authentication, real-time data storage, notification management, and service schedule handling. Testing was conducted using the Black Box method to evaluate functionality without examining the source code. The results showed that features such as login, registration, service selection, scheduling, and notifications performed as expected. Feasibility evaluation involving 47 respondents through questionnaires indicated a high level of satisfaction, with percentage scores ranging from 83.51% to 91.85%. The application successfully improves the efficiency of reservation processes and facilitates real-time reservation data management. The findings conclude that this application effectively addresses issues related to manual reservation systems. Future development may include adding online payment features and enhancing application performance to improve user experience